Climate Services Transformed: Decision-Making Practice for the Coast in a Changing Climate - Lawrence, Judy; Stephens, Scott; Blackett, Paula; Bell, Robert G.; Priestley, Rebecca (Frontiers in Marine Science, 2021)
Climate services play an important role in informing decision makers about how to reduce the impact of climate-related hazards, by building capacity through access to relevant data and information globally and regionally. Different types of climate services include long-term warning systems, projections, monitoring/triggers and signals, risk evaluation tools, and behavior change tools. However, climate services are often promoted as “improving uptake” and “translating and communicating science” This framing, which assumes that climate services are developed by scientists and “provided” to users, has limitations for decision makers designing actions to address changing coastal hazard risk driven by sea-level rise. Acting upon the IPCC 1.5 Degree Special Report imperative for urgent actions to reduce exposure and vulnerability at the coast will require a transformation in the way climate services are developed and delivered, in tandem with an understanding of the decision-making and policy context. Tools and policies must explicitly address deepening uncertainty and changing risk over long timeframes. Their use also must be compatible with the jurisdiction’s institutional frameworks and decision-making practice and relevant to user needs as changing risks unfold. Attention to both short- and long-term decisions are paramount to avoid lock-in and path dependency of decisions taken today, and to ensure relevance for the timeframes of investments in infrastructure and settlements. This requires actionable science and usable tools developed through multi-disciplinary efforts by scientists, co-producing them with decision agencies and communities. We give examples of different types of climate services developed with users and draw out some universal lessons learned in developing and applying them in New Zealand.